Tumor organoids for primary liver cancers: A systematic review of current applications in diagnostics, disease modeling, and drug screening - Ayesha A. Qureshi; Chase J. Wehrle; Sofia Ferreira-Gonzalez; Chunbao Jiao; Hanna Hong; Neda Dadgar; Jorge Arpi-Palacios; Yee Phoon Phong; Jaekeun Kim; Keyue Sun; Koji Hashimoto; David CH. Kwon; et al. (JHEP Reports)
Background & Aims: Liver cancer-related deaths are projected to exceed one million annually by 2030. Existing therapies have significant limitations, including severe side effects and inconsistent efficacy. Innovative therapeutic approaches to address primary liver cancer (PLC) have led to the ongoing development of tumor-derived organoids. These are sophisticated three-dimensional structures capable of mimicking native tissue architecture and function in vitro, improving our ability to model in vivo homeostasis and disease. Methods: This systematic review consolidates known literature on human and mouse liver organoids across all PLC subtypes, emphasizing diagnostic precision, disease modeling, and drug screening capabilities. Results: Across all 39 included studies, organoids were most frequently patient-derived, closely followed by cancer cell line-derived. The literature concentrated on hepatocellular carcinoma and intrahepatic cholangiocarcinoma, while exploration of other subtypes was limited. These studies demonstrate a valuable role for PLC organoid cultures in biomarker discovery, disease modeling, and therapeutic exploration. Conclusions: Encouraging advances such as organoid-on-a-chip and co-culturing systems hold promise for advancing treatment regimens for PLC. Standardizing in vitro protocols is crucial to integrate research breakthroughs into practical treatment strategies for PLC. Impact and implications:: This study provides an overview of the current understanding of tumor-derived organoids in primary liver cancers, emphasizing their potential in diagnostics, disease modeling, and drug screening. The scientific foundation rests on the organoids' ability to replicate the tumor microenvironment and genetic landscape, opening new avenues for personalized therapies. These insights are crucial for both researchers and clinicians, as patient-derived organoids can help identify biomarkers and therapeutic targets. Physicians and policymakers can harness these advances to drive progress in precision medicine, while recognizing the challenges involved in standardizing organoid models for clinical implementation.